Aesthetics on French Style A Critique on the Book Aesthetics of Photography - Mohammad Khodadadi Motarjemzadeh (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
This article tries to analyze and critique the book Aesthetics of Photography, according to set criteria. Francois Soulages, the author of this book, is an experienced professor in the field of aesthetics and philosophy of art in France. The book has an acceptable quality of print and published. There are few typographical errors, fluent prose, and footnotes, references, indexes, and bibliographies. Despite a few minor flaws, the book sounds well.  The translation of the book to Persian is also fine. Thematic variety and proper distribution of the book's contents in three general sections and 12 chapters have been done very cleverly. In terms of content, the book has been able to challenge the issues related to the aesthetics of photography from different perspectives and useful case studies. By constantly using the method of dialectical reasoning between conventional and unconventional metrics (in terms of type and time), Soulages has done very well in understanding the concepts of contemporary photographic aesthetics from the standpoint of a French expert and has been able to provide a useful perspective on contemporary aesthetic effects. The introduction of some influential photographers of late is also one of the desirable contributions of the book. The book contains very useful information for the university photography community in our country.